2020
DOI: 10.1021/acs.jafc.0c04615
|View full text |Cite
|
Sign up to set email alerts
|

Nineteen New Flavanol–Fatty Alcohol Hybrids with α-Glucosidase and PTP1B Dual Inhibition: One Unusual Type of Antidiabetic Constituent from Amomum tsao-ko

Abstract: The dried fruits of Amomum tsao-ko were first revealed to have hypoglycemic effects on db/db mice at a concentration of 200 mg/kg. In order to clarify the antidiabetic constituents, 19 new flavanol−fatty alcohol hybrids, tsaokoflavanols A−S (1−19), were isolated and determined by extensive spectroscopic data and ECD calculations. Most of the compounds showed α-glucosidase and PTP1B dual inhibition, among which 1, 2, 6, 11, and 18 exhibited obvious activity against α-glucosidase with IC 50 values of 5.2−9.0 μM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The α -glucosidase inhibition activity was investigated by a spectrophotometric method as previous researches [ 12 , 14 16 , 18 ]. Acarbose (Bayer Healthcare Co Ltd, Beijing, China) was utilized as a positive control and was dissolved in phosphate buffer (PB, 0.1 mM, pH = 6.8).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The α -glucosidase inhibition activity was investigated by a spectrophotometric method as previous researches [ 12 , 14 16 , 18 ]. Acarbose (Bayer Healthcare Co Ltd, Beijing, China) was utilized as a positive control and was dissolved in phosphate buffer (PB, 0.1 mM, pH = 6.8).…”
Section: Methodsmentioning
confidence: 99%
“…The PTP1B inhibition assay was investigated by the method as previous reports [ 14 , 16 , 18 ]. Working buffer containing MOPS (34.5 mM), DTT (1.9 mM), EDTA·4Na (0.67 mM), BSA (2.0 mg/mL), and NaCl (2.1 mM) in deionized water was prepared before the assay.…”
Section: Methodsmentioning
confidence: 99%
“…5 ) (He et al 2020c ), flavanol-fatty alcohol hybrids ( 123 – 141, Fig. 5 ) (He et al 2020a ), flavanol-monoterpenoid hybrids ( 142 , 143, Fig. 5 ) (He et al 2020b ), diarylheptanoids ( 144 – 188 , Fig.…”
Section: Phytochemistrymentioning
confidence: 99%
“…Phytochemical research revealed at least 209 compounds belonging to terpenoids, flavonoids, diarylheptanoids, and organic acids were present in Tsaoko Fructus (Hong et al 2015 ; Lee et al 2019 ; He et al 2020d ). Some of them have anti-biotic, anti-inflammatory, anti-tumor, anti-diabetic, and neuroprotective activities (Zhang et al 2014 , 2015 ; Kim et al 2016 ; Lee et al 2019 ; He et al 2020a , d ).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a chronic metabolic disease that is characterized by hyperglycemia, and more than 90% diabetic patients have Type 2 Diabetes Mellitus (T2DM) [17]. α-Glucosidase inhibitors are widely used in the treatment of type 2 diabetes [18]. Alzheimer's disease (AD) is a common degenerative disease of the central nervous system that is characterized by memory and cognitive dysfunction and the decreased ability to perform daily living activities [19].…”
Section: Introductionmentioning
confidence: 99%